The Effect of the Unemployment and Population Growth on the Level of Poverty in Discrits/Cities Throughout the Nias Archipelago - Zagoto*, Sri Endang Putri; Tanjung, Ahmad Albar; Sukardi, Sukardi; Nasution, M. Ardi Rafian (Universitas Syiah Kuala, 2023)
This study uses secondary data with panel data analysis tools, consisting of time series data during the 2015-2021 period and cross section data for 5 districts/cities in the Nias Island. The analysis model used in this study to estimate the panel data regression model is to use the Fixed Effect Model. The results in the study with a significance level of 5% show that (1) the unemployment variable has a significant effect on the poverty rate; (2) the population growth variable has a significant effect on the poverty rate.